Oxidative stress, neurotoxicity, and non-specific immune responses in juvenile red sea bream, Pagrus major, exposed to different waterborne selenium concentrations. (September 2015) - Kim, Jun-Hwan; Kang, Ju-Chan
Highlights: The antioxidant enzymes of Pagrus major were considerably increase by Se exposure. The AChE activity was significantly inhibited by Se exposure. The significant changes were observed in non-specific immune parameters. Abstract: Juvenile Pagrus major (mean length 15.8 ± 1.6 cm, and mean weight 90.4 ± 4.7 g) were exposed for 4 weeks with waterborne selenium concentration (0, 50, 100, 200, and 400 μg L −1 ). In oxidative stress indicators, liver and gill superoxide dismutase (SOD) activity and glutathione S-transferase (GST) activity were markedly elevated after 4 weeks exposure. Similarly, glutathione (GSH) level in liver and gill was also increased in response to the highest Se exposure after 4 weeks exposure. In neurotoxicity, AChE activity was inhibited in brain and muscle tissues by waterborne Se exposure. In the non-specific immune responses, lysozyme activity of plasma and kidney was significantly increased by waterborne Se exposure. Peroxidase activity and anti-protease activity were decreased at high Se concentration. The results suggest that waterborne Se exposure can induce significant oxidative stress, inhibition of AChE activity, and immunological alterations.